Ca2+ binding and translocation by the sarcoplasmic reticulum ATPase: Functional and structural considerations. Issue 5 (October 1995) - Inesi, Giuseppe; Chen, Li; Sumbilla, Carlota; Lewis, David; Kirtley, Mary E.
Abstract : Three experimental systems are described including sarcoplasmic reticulum (SR) vesicles, reconstituted proteoliposomes, and recombinant protein obtained by gene transfer and expression in foreign cells. It is shown that the Ca 2+ ATPase of sarcoplasmic reticulum (SR) includes an extramembranous globular head which is connected through a stalk to a membrane bound region. Cooperative binding of two calcium ions occurs sequentially, within a channel formed by four clustered helices within the membrane bound region. Destabilization of the helical cluster is produced following enzyme phosphorylation by ATP at the catalytic site in the extramembranous region. The affinity and orientation of the Ca 2+ binding site are thereby changed, permitting vectorial dissociation of bound Ca 2+ against a concentration gradient. A long range linkage between phosphorylation and Ca 2+ binding sites is provided by an intervening peptide segment that retains high homology in cation transport ATPases, and whose function is highly sensitive to mutational perturbations.